0107 A Collaborative Approach To Improving Training Through Simulation - The Journey!. (1st November 2014) - Nicklin, Jane; Ford, Kay
Abstract : Background: Collaboration is defined as ' something created by working jointly with another or others'. 1 One of the key objectives in the Health Education Yorkshire and the Humber - 2014–2018 Clinical Skills and Simulation 5-year plan is ' to create a culture of effective multi-professional partnerships and collaborative working at local, regional and national levels'. 2 Simulation has historically been used by medical devices companies in the manufacturing process to improve performance and costs 3, however a proportion recognise that simulation only plays a small part within their training packages offered to the user. Description of innovation or topic: A current pilot project is providing the opportunity for industry, Trusts and the HEYH Strategic Clinical Skills Advisors to facilitate 4 workshops across the region incorporating interactive simulation scenarios and debrief alongside the product underpinning theoretical information and skills practice. Methodology: Initial engagement, selection of centres, identifying expert faculty and technical support required from all parties, ascertain equipment and manikin resources available, plan dates and programme, run the workshops, evaluate the development process using Gibbs reflective cycle, consider changes as appropriate. Potential impact: Share knowledge, expertise and best practice Help to inform and drive the development of appropriate, standardised, quality training Mutual support between organisations Opportunity for skills and simulation centres to extend their remit and provision of courses Video material generated for marketing and training purposes Greater understanding of the product for future procurement Increase awareness, knowledge and skill of the user, thus improve patient outcomes and safety Pre, post and follow-up evaluation data for all participants Potential impact: The method used to roll-out this pilot has the potential to be used as a blue-print for future projects involving multi-agency, multi-professional collaboration, initial feedback is positive and will be used to inform overall evaluation of the pilot project. References: Collins English Dictionary - Complete and unabridged 10 th edition 2009 William Collins Sons and Co. Ltd Health Education Yorkshire and the Humber - 2014-2018 Clinical Skills and Simulation 5-year plan Annex A http://simul8healthcare.com/medical-device-companies/ (Accessed 04/05/14)